Program Pengembangan Bimbingan Belajar Untuk Anak Anak Desa Hambiri Tahun 2023 - Akbar hasan habibi; Israk Khadijah Riski lubis; Mirna Khairani; Sauwitri Pospos; Rina Mawaddah; Sukma Andini; Maulana Maulana; Risna Khasanah Nasution; Ali Al Husein (Pusat Riset dan Inovasi Nasional, 2024)
Interest in learning and lack of motivation are the main problems faced by students in Hambiri Village. It can be seen that children in Hambiri Village have a lack of awareness about education, therefore the importance of tutoring which will motivate students to be aware of the importance of education for the future. So we, KKN group 37 Stain Mandailing Natal students, aim to hold tutoring activities to increase interest in learning for elementary school age students in Hambiri Village. Tutoring is one of our work programs for the 37 Stain Mandailing Natal group, especially in the field of education. This service research focuses on students in Hambiri Village. The research method used is descriptive qualitative. Based on research results, this tutoring activity has had a significant impact in terms of general and religious knowledge, such as increasing children's understanding, growing children's awareness of learning, children being more active in discussing and asking questions about material they don't understand, and increasing interest in participating in activities. the study guidance.